2020
DOI: 10.1016/j.idairyj.2020.104832
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of novel Lactococcus lactis strains against Salmonella Typhimurium DT12, Escherichia coli O157:H7 VT− and Klebsiella pneumoniae in raw and pasteurised camel milk

Abstract: The present study investigated inhibition of multiple food related pathogens in raw and pasteurised camel milk during fermentation with four novel Lactococcus lactis strains. All pathogens alone in camel milk reached 8.0 log(CFU mL -1 ). When the pathogens were cultivated with L. lactis MS22333 or MS22337 they were reduced between 0.9-6.0 log(CFU mL -1 ). L. lactis MS22314 and MS22336 showed no antimicrobial activity.Bad hygiene and lack of cooling facilities have resulted in spontaneously fermented African ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Food safety incidents caused by food-borne pathogen biofilms have attracted wide research attention. Many different antibacterial treatments have been used to eliminate or reduce the ability of food-borne pathogens to form biofilms [26][27][28]. Li et al [29] found that ultrasonic treatment caused multi-target inactivation of S. aureus and E. coli due to different degrees of irreversible damages to the cell wall and plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Food safety incidents caused by food-borne pathogen biofilms have attracted wide research attention. Many different antibacterial treatments have been used to eliminate or reduce the ability of food-borne pathogens to form biofilms [26][27][28]. Li et al [29] found that ultrasonic treatment caused multi-target inactivation of S. aureus and E. coli due to different degrees of irreversible damages to the cell wall and plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, existence of Klebsiella pneumoniae in raw milk also remains a nonnegligible problem. Bragason et al (2020) discovered that the L. lactis strains isolated from camel milk can inhibit the growth of food-related pathogens in both raw and pasteurized camel milk, providing new ideas for the prevention and treatment of K. pneumoniae in raw milk. It offers a feasible solution to add microbial agents that inhibit pathogenic bacteria to dairy cow feed in pastures.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have isolated new strains of lactic acid bacteria from raw CM that kill even very large numbers of different pathogens [8]. Additionally, the fermentation and enzymatic hydrolysis of camel protein produce different types of bioactive peptides exerting different activities in in vitro and in vivo [9] [10].…”
Section: Unique Compositionmentioning
confidence: 99%